The Incidence of Payroll Taxation: Evidence from Chile - Gruber, Jonathan (Journal of Labor Economics, 1997)
I provide new evidence on the incidence of payroll taxation by examining the experience of Chile before and after the privatization of its Social Security system. This policy change led to a sharp exogenous reduction in the payroll tax burden on Chilean firms; on average, payroll tax rates fell by 25% over 6 years. Using data from a census of manufacturing firms, I estimate that the incidence of payroll taxation is fully on wages, with no effect on employment. This finding is robust to a variety of empirical approaches to the problem of measurement error in firm‐level measures of taxes/worker.